2019
DOI: 10.3389/fphar.2019.00654
|View full text |Cite
|
Sign up to set email alerts
|

Star Allele-Based Haplotyping versus Gene-Wise Variant Burden Scoring for Predicting 6-Mercaptopurine Intolerance in Pediatric Acute Lymphoblastic Leukemia Patients

Abstract: Nudix Hydrolase 15 (NUDT15) and Thiopurine S-Methyltransferase (TPMT) are strong genetic determinants of thiopurine toxicity in pediatric acute lymphoblastic leukemia (ALL) patients. Since patients with NUDT15 or TPMT deficiency suffer severe adverse drug reactions, star (*) allele-based haplotypes have been used to predict an optimal 6-mercaptopurine (6-MP) dosing. However, star allele haplotyping suffers from insufficient, incons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…22 Compared with other Asian ALL populations, 13,[23][24][25][26][27] the frequency of TPMT Ã 3C in this Thai pediatric ALL population was somewhat higher but did not reach statistical significance except with the Korean population. 28,29 In addition, the allele frequency TPMT Ã 3C in our study population was extremely higher than those reported in European ALL patients 30 (►Table 2). Among 10 NUDT15 variants investigated, NUDT15 Ã 3 is the most common variant in Thai ALL population, followed by NUDT15 Ã 6, NUDT15 Ã 2, and NUDT15 Ã 5 variants.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…22 Compared with other Asian ALL populations, 13,[23][24][25][26][27] the frequency of TPMT Ã 3C in this Thai pediatric ALL population was somewhat higher but did not reach statistical significance except with the Korean population. 28,29 In addition, the allele frequency TPMT Ã 3C in our study population was extremely higher than those reported in European ALL patients 30 (►Table 2). Among 10 NUDT15 variants investigated, NUDT15 Ã 3 is the most common variant in Thai ALL population, followed by NUDT15 Ã 6, NUDT15 Ã 2, and NUDT15 Ã 5 variants.…”
Section: Discussioncontrasting
confidence: 70%
“…Other known loss-of-function alleles were not detected in this study population. Compared with other Asian ALL populations, 4,21,24,28,[31][32][33] the frequency of the NUDT15 Ã 3 in Thai pediatric ALL patients was comparable, whereas NUDT15 Ã 6 was significantly higher. In contrast, the allele frequency of NUDT15 Ã 3 observed in this study was higher than those reported in European, 14 Hispanic-American, 14 Native-American, 4 and African 14 ALL populations (►Table 4).…”
Section: Discussionmentioning
confidence: 57%
“…[21] This method operates under the hypothesis that variants that potentially change protein function are not assured, but may cause deleterious phenotypes. [22] A lower GVB score represents an increased likelihood of a variant to be more deleterious to the function of the protein encoded by the gene. [21,22]…”
Section: Methodsmentioning
confidence: 99%
“…[22] A lower GVB score represents an increased likelihood of a variant to be more deleterious to the function of the protein encoded by the gene. [21,22]…”
Section: Methodsmentioning
confidence: 99%
“…Since East Asian ancestry requires significantly lower 6-MP dose intensity compared to the other ethnic groups [5], patients who require less than 25% of the protocol planned dose were classified as MP-intolerant groups [6]. We have previously presented a detailed description of the subjects and a summary of the measurements [7]. The present study was approved by the SNUH, AMC, and SMC institutional review boards.…”
Section: Subjectsmentioning
confidence: 99%